Dampak Pandemi Covid-19 terhadap User Experience pada Perpustakaan Digital - Orisa Mahardhini; Indira Irawati (Institut Agama Islam Negeri Salatiga, 2021)
The user interface of digital libraries during the special conditions of the COVID-19 pandemic is one of the leading indicators that need attention from libraries. Library users will always choose easy access, fast and recommended by library users by word of mouth. The User Interface will affect the user experience in using the digital library. This research is essential to find out the description of user experience in using digital libraries during the COVID-19 pandemic. This study aims to describe the user experience, which includes emotions, perceptions, attitudes, and responses in using digital libraries. This study uses a qualitative approach with a systematic literature review method using the Systematic Literature Review (SLR) software guide from Kitchenham. User experience in using digital libraries is influenced by emotions and perceptions of digital library users because the urgency of using digital library services is increasingly substantial during the pandemic. In conclusion, the impact of the COVID-19 pandemic has affected the user experience, especially in the crisis that has created user awareness to use digital libraries. Considering that research related to User Experience in digital libraries during the COVID-19 pandemic is still lacking, the researchers suggest that further research be carried out with a quantitative approach to obtain valid data.